I'm supposed to solve this question using the Substitution Method.

Thank you for the opportunity to help you with your question!

let 5-z=x

therefore,

8x^2-15x+3=0

x=-b+-sqrt(b^2-4ac)/2a

x=15+sqrt(129)/16 or x=15-sqrt(129)/16

x=0.2276 or x=1.6473

z=5-0.2276 or z=5-1.6473

z=4.7724 or z=3.3527

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up